Ethnobothany of Medicinal Plants Utilized by the People of Nagari Campago District V Koto Kampung Dalam Padang Pariaman Regency - Audela Irma Oktavira (Department of Biology, Faculty of Mathematics and Natural Sciences, Universitas Negeri Padang, 2023)
Indonesia is a country that has high biodiversity including plants. Plants are often used to fulfill human needs, including physical needs, such as traditional medicines for body health. Plants that have medicinal properties are used to relieve pain, kill pathogens and are able to increase endurance. The aim of this study is to find out the species of medicinal plants dan the benefits, the parts of plant used and the method of processing them based on the knowledge of the people of Nagari Campago District V Koto Kampung Dalam Padang Pariaman Regency. Data collected through semi- structured interviews with 20 selected respondents who had knowledge more about the use of plants as traditional medicine. Based on the results of the study, 30 types of medicinal plants from 21 families were used by the people of Nagari Campago. The most parts of plant used are leaves (60%) and the method of processing is mostly done by boiling (67%) in the singular form and consumed by drinking (90%).